2007
DOI: 10.1016/j.cplett.2007.05.080
|View full text |Cite
|
Sign up to set email alerts
|

Protein dynamical transition in terahertz dielectric response

Abstract: The 200 K protein dynamical transition is observed for the first time in the teraherz dielectric response.The complex dielectric permittivity ε = ε' + iε" is determined in the 0.2 -2.0 THz and 80-294 K ranges.ε" has a linear temperature dependence up to 200 K then sharply increases. The low temperature linear dependence in ε" indicates anharmonicity for temperatures 80 K < T < 180 K, challenging the assumed harmonicity below 200K. The temperature dependence is consistent with beta relaxation response and shows… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 26 publications
4
67
0
Order By: Relevance
“…16 A well-defined dynamical transition related to biomolecule functioning above specific hydration levels (27% w/w), or temperatures (above 200 K), is detectable in THz spectrum. [16][17][18][19][20] Another study reveals the existence of structural collective modes for cytochrome c protein. 15 Solvated proteins (lysozyme and bovine serum albumin (BSA)), along with alcohols, have been also studied at different concentrations by micro-fluidic systems 4,21 over 50-110 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…16 A well-defined dynamical transition related to biomolecule functioning above specific hydration levels (27% w/w), or temperatures (above 200 K), is detectable in THz spectrum. [16][17][18][19][20] Another study reveals the existence of structural collective modes for cytochrome c protein. 15 Solvated proteins (lysozyme and bovine serum albumin (BSA)), along with alcohols, have been also studied at different concentrations by micro-fluidic systems 4,21 over 50-110 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…This concept was applied to study a wide range of molecular interactions of biomolecules during solvation: lactose; 78 threhalose, lactose, and glucose; 79 among others. In addition, very interesting effects regarding the hydration of biomolecules were detected using terahertz spectroscopy, [90][91][92] including the protein dynamic transition 93,94 and lipid-membrane formation. 95,96 More detailed reviews of these topics have been published.…”
Section: Mesoscopic Structure and Dynamicsmentioning
confidence: 99%
“…This could be particularly useful when considering the practical difficulties in terms of expense and beam time availability to perform neutron scattering measurements, which makes it an unsuitable technique for routine analysis of a large number of samples. As an example, neutron scattering has proven to be useful in determining the dynamical transition of solvated proteins by examining the means square displacement u 2 [27] and it has been since demonstrated that similar information can be extracted using THz-TDS [28,29].…”
Section: Comparison Of Terahertz Spectroscopy To Scattering Techniquesmentioning
confidence: 99%